Cherubism: Report of a regressed nonfamilial grade 1 case - Mysore K Sunil; Ashwarya Trivedi; Aarti Trakroo; Neetu Singla (Wolters Kluwer Medknow Publications, 2014)
Cherubism is a rare non-neoplastic fibro-osseous disorder characterized by clinically evident bilateral painless enlargement of the jaws that usually gives a cherubic appearance. Major complications may occur along with the presence of facial deformities. The facial deformities may frequently be associated with dental malformations. Bilateral swelling of the jaws usually appears between the age of 2 and 7 years, after which, the lesions proliferate and increase in size until puberty. These lesions subsequently begin to regress, fill with bone and remodel until the age of 30 years. Following this, the lesions frequently become undetectable clinically, due to which, many affected adults have a normal facial appearance. Here, we report a case of a 22-year-old female patient suffering from cherub-like appearance with regressed features.